Descriptive Analysis of the Impact of a Cashless Society on Gen Z Spending Patterns - Bella Benia Akhiri; Dea Arme Tiara Harahap (Rescollacom (Research Collaborations Community), 2026)
The phenomenon of a cashless society has fundamentally transformed Generation Z’s consumption behavior through the increased adoption of digital payment methods such as e-wallets, digital bank transfers, and QRIS. This descriptive study analyzes primary data from 100 Generation Z respondents (aged 17–27 years) in Sukabumi Regency using a questionnaire instrument based on a 5-point Likert scale and frequency distribution analysis. The results show that the frequency of cashless usage reaches 5–20 times per month for 68% of respondents, with high mean scores for perceptions of ease of daily payments (4.35 ± 0.72), transaction efficiency compared to cash (4.43 ± 0.71), and time savings in online shopping (4.40 ± 0.72). However, a significant increase in impulsive buying behavior was identified, occurring 3–5 times per month among 48 respondents, along with moderate perceptions of inclusive accessibility for all segments of society (3.92 ± 0.84) and data security risk (3.55 ± 1.23). These findings are consistent with the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), leading to recommendations for strengthening digital financial literacy education, improving network infrastructure, and developing impulse-control features within payment applications.